Vascular Thrombosis in Severe COVID-19 Requiring Extracorporeal Membrane Oxygenation: A Multicenter Study. Issue 4 (27th September 2021) - Weir-McCall, Jonathan R.; Galea, Gabriel; Mun Mak, Sze; Joshi, Kushal; Agrawal, Bobby; Screaton, Nicholas; Toshner, Mark; Ruggiero, Alessandro; Benedetti, Giulia; Brozik, Jan; Machin, Ruth; Das, Indrajeet; et al.
Abstract : OBJECTIVES: Coronavirus disease 2019 has been reported to be a prothrombotic condition; however, multicenter data comparing this with other viral pneumonias in those requiring extracorporeal membrane oxygenation are lacking. We conducted a multicenter study using whole-body CT to examine the prevalence, severity, and nature of vascular complications in coronavirus disease 2019 in comparison with patients with other viral pneumonias. DESIGN: We analyzed whole-body CT scans for the presence of vascular thrombosis (defined as pulmonary artery thrombus, venous thrombus, systemic arterial thrombus, or end-organ infarct). The severity, distribution, and morphology of pulmonary artery thrombus were characterized. Competing risk cumulative incidence analysis was used to compare survival with discharge. SETTING: Three centers of the English national extracorporeal membrane oxygenation service. PATIENTS: Consecutive patients admitted with either coronavirus disease 2019 or noncoronavirus disease 2019 viral pneumonia admitted from January 2019. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: One-hundred thirty-six patients (45.2 ± 10.6 yr old, 39/146 [27%] female) requiring extracorporeal membrane oxygenation support underwent whole-body CT scans at admission. Of these, 86 had coronavirus disease 2019 pneumonia, and 50 had noncoronavirus disease 2019 viral pneumonia. Vascular thrombosis was seen more often in patients with coronavirus disease 2019 (odds ratio, 12.9 [95% CI 4.5–36.8]). In those with coronavirus disease 2019, 57 (73%) demonstrated pulmonary artery thrombus or pulmonary perfusion defects. Eighty-two percent of thrombus exhibited emboli-like morphology. The location of pulmonary artery thrombus and parenchymal perfusion defects was only concordant in 30% of cases. The risk of mortality was higher in those with coronavirus disease 2019 compared with noncoronavirus disease 2019 pneumonia (χ 2 = 3.94; p = 0.047). Mortality was no different in coronavirus disease 2019 patients with or without vascular thrombosis (χ 2 = 0.44; p = 0.51). CONCLUSIONS: In patients who received extracorporeal membrane oxygenation, coronavirus disease 2019 is associated with a higher prevalence of vascular thrombosis compared with noncoronavirus disease viral pneumonias. The pattern of pulmonary vascular changes suggests concurrent embolic disease and small vessel disease. Despite this, vascular thrombosis was not linked to poorer short-term prognosis in those with coronavirus disease 2019.